“The Pandemic is Just Happening on Top of a Pandemic for Us”. Unpaid Carers’ Experiences of Lockdown in the UK: A Thematic Analysis - Emily Moultrie; Jaimee Sheila Mallion; Charlotte Taylor-Page (Journal of Long-Term Care, 2024)
Context: With reduced access to medical and social support during the COVID-19 pandemic, the level of support provided by unpaid carers over the lockdown period in the UK was higher than ever. However, the experience of unpaid carers during this period is often overlooked.